Relevansi Penguasaan Nahwu dan Sharf dengan Kemampuan Membaca Teks-Teks Keagamaan Teungku Dayah Aceh - Aan Muhammady; Danial Jamal (Institut Agama Islam Negeri Metro, 2022)
This research is important to discuss based on the phenomenon of teungku dayah errors in reading religious texts in Aceh. This study aims to determine the relevance between mastery of Nahwu and Sharf with the ability to read religious texts owned by tengku dayah and examine the causal factors from the perspective of Nahwu and Sharf. Dayah Darussalam, Labuhan Haji, South Aceh District, was chosen as the research location because it is one of the oldest in Aceh. This study uses field research methods with a qualitative approach. The data were obtained from in-depth interviews, observation, and documentation of the curriculum applied at the dayah. All the data obtained were analyzed descriptively and qualitatively. The study results show that learning Nahwu and Sharf in the Acehnese dayah is generally carried out in two types of learning programs: regular and extracurricular. Teungku Dayah's ability to read religious texts in Aceh could be much higher. This is indicated by the many mistakes they made when reading religious texts, both in terms of Nahwu and Sharf. Among the contributing factors is the absence of a dayah curriculum related to active Arabic practice and tahsin al-Qur'an.